Getting the Final Girl Out of Get Out. - Wilz, Kelly (Women's Studies in Communication, 2021)
Get Out does not conform to the general expectations of horror films but instead plays with, inverts, and makes light of horror tropes. The slasher subgenre is a recognizable form that recurs in the public imaginary, but what we see in this film is repetition with a difference that reveals how recurring patterns can be reiterated in destabilizing ways. Here the "return of the repressed" is monstrous whiteness and white supremacy, which have been denied, or disavowed, in a "postracial" culture. When they return, they literally consume Black bodies, commandeering them for white use. Through this reading of Get Out, I intend to rethink the trope of the "Final Girl" as it is positioned within the slasher subgenre and to consider how that position not only provides context for current political moments but also shifts in the horror genre itself.